Dampak Penerapan Good Governance, Sistem Informasi Akuntansi dan Sistem Pengendalian Internal Terhadap Kinerja Instansi Pemerintah - Heluka, Rosen; Pattiasina, Victor; Sutisman, Entar; Bonsapia, Melyanus; Patiran, Andarias (Program Studi Administrasi Niaga STIA Said Perintah, 2022)
This study examines the effect of implementing good governance, accounting information systems, and internal control systems on the performance of Yahokimo district government agencies. testing was carried out on a sample of 97 respondents. The sample method used is purposive sampling. data collection is done by direct survey. Hypothesis testing was tested empirically using moderated regression. The results showed that the implementation of Good Governance had a significant positive effect on the Performance of the Yahokimo Regency Government Agencies, the Accounting Information System had a significant positive effect on the Performance of the Yahokimo Regency Government Agencies, the Internal Control System had a significant positive effect on the Performance of the Yahokimo Regency Government Agencies and the influence of the Implementation of Good Governance, Information Systems Accounting and Internal Control Systems simultaneously affect the Performance of Government Agencies of Yahokimo Regency.